2022
DOI: 10.1177/09544062221089180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phase difference and stiffness ratio on fretting fatigue behavior under variable normal load conditions

Abstract: This paper investigated the effect of variable normal load on the fretting fatigue mechanism. A kinetics-based Q- P curve analysis method was proposed to assist testing system design and experiment result analysis. Based on this method, a biaxial fretting fatigue testing system was designed. Experimental and numerical investigation was carried out to discuss the effect of biaxial loading phase difference (the phase difference between bulk load and cyclic normal load) and stiffness ratio (the stiffness ratio be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The fretting fatigue lives range from 4 3 10 5 to 1 3 10 6 . More details about the experiment is shown in Li et al 31 The numerical assistant calculation model As the fretting process under VNL conditions is very complicated, an FEA model was established to assist in the analysis of this problem. As shown in Figure 7, a 2-D plane-strain model (based on the geometry and structure of the specimen and pad used in the test) was established using FEA software ABAQUS to calculate the contact process under the cyclic normal load and bulk load.…”
Section: The Experimental Evaluation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fretting fatigue lives range from 4 3 10 5 to 1 3 10 6 . More details about the experiment is shown in Li et al 31 The numerical assistant calculation model As the fretting process under VNL conditions is very complicated, an FEA model was established to assist in the analysis of this problem. As shown in Figure 7, a 2-D plane-strain model (based on the geometry and structure of the specimen and pad used in the test) was established using FEA software ABAQUS to calculate the contact process under the cyclic normal load and bulk load.…”
Section: The Experimental Evaluation Methodsmentioning
confidence: 99%
“…The fretting fatigue lives range from 4 × 10 5 to 1 × 10 6 . More details about the experiment is shown in Li et al 31…”
Section: Establishment Of the Q-p Curves Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, especially in the past decade, a lot of research interest was dedicated to the impact of the loading protocol and the contact profile geometry on crack initiation, as these are influence factors that can be controlled more or less easily in design and construction of fretting contacts. With respect to the loading protocol, the influences of out-of-phase loading [10] and phase difference ( [11,12]) (however, mainly with focus on a phase difference between bulk stresses and contact loads), as well as more complex cyclic loading paths ( [13,14]), were studied. On the other hand, regarding the influence of the surface geometry on crack initiation, the overall contact geometry ( [15,16]) and macroscopically worn profiles [17], as well as the surface microgeometry [18], surface pit treatment [19] and machined surface texture [20] have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al 13 found that despite railway axles enduring low fatigue stress, severe stress concentration occurred within the contact surface due to wear, leading to the initiation of multi‐site cracks. Li et al 14 used the cylinder‐on‐flat contact configurations to investigate the fretting fatigue in consideration of fretting wear. They found that under the partial slip condition, the fretting wear was scant and fretting fatigue presented as a multi‐site crack behavior; while under the gross slip condition, the wear was severe and fretting fatigue presented as a single‐site crack behavior.…”
Section: Introductionmentioning
confidence: 99%